2017
DOI: 10.1007/978-981-10-7233-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Drops, Jets and High-Resolution 3D Printing: Fundamentals and Applications

Abstract: The ability to print high-resolution (< 10 µm) three-dimensional (3D) features is important in numerous existing and emerging applications such as tissue engineering, nanoelectronics, photovoltaics, optics, biomedical devices etc. The current chapter is focused on a subset of high-resolution printing techniques that exploit micro and nanofluidics features to attain high resolution. Here these approaches are referred as fluidics assisted high-resolution 3D printing. Salient examples of such techniques are elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
(170 reference statements)
0
3
0
Order By: Relevance
“…1,2 The resultant wetting from the droplet−surface interactions is a central theme in many applications such as spray cooling, 3−5 spray coating, 6,7 spray combustion, 8 inkjet printing, 9 3Dprinting, 10,11 ceramics, 12 and metals. 13 The spreading behavior of droplets on dry surfaces is governed by a balance between the inertial, viscous, and surface tension forces. The droplet's spreading characteristics can have markedly different outcomes due to surface roughness and surface wettability through the contact angle it makes with the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The resultant wetting from the droplet−surface interactions is a central theme in many applications such as spray cooling, 3−5 spray coating, 6,7 spray combustion, 8 inkjet printing, 9 3Dprinting, 10,11 ceramics, 12 and metals. 13 The spreading behavior of droplets on dry surfaces is governed by a balance between the inertial, viscous, and surface tension forces. The droplet's spreading characteristics can have markedly different outcomes due to surface roughness and surface wettability through the contact angle it makes with the surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The resultant wetting from the droplet–surface interactions is a central theme in many applications such as spray cooling, spray coating, , spray combustion, inkjet printing, 3D-printing, , ceramics, and metals …”
Section: Introductionmentioning
confidence: 99%
“…A previous study has demonstrated the use of custom-made nozzles with a microcapillary with minimum filament size down to 1 μm (with D c = 0.5–5 μm) . The decrease in D c causes a pronounced increase in pressure drop across the nozzle (Δ P ∼ 1/ D c 4 for Newtonian fluids) . The use of nozzles with small D c is therefore limited by the applicable pressure to the system.…”
Section: Resultsmentioning
confidence: 99%